2022
DOI: 10.3389/fpls.2022.853309
|View full text |Cite
|
Sign up to set email alerts
|

Empowering roots—Some current aspects of root bioenergetics

Abstract: Roots of higher plants provide the shoot with nutrients and water. In exchange, they receive photosynthates, which serve both as energy source and building blocks for maintenance and growth. While studies in plant bioenergetics used to focus on photosynthesis, several more recent findings also aroused or renewed interest in energy conversion and allocation in roots. Root building costs were identified as a long-undervalued trait, which turned out to be highly relevant for stress tolerance and nutrient use effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 125 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…Our experimental and modelling results indicate that some of these assumptions need revisiting. We showed that the intensity of water stress, as the result of the growing environment or intra-speci c plant competition, can affect both the maximum rooting depth and the depth at which crops will use water, indicating changes in resource allocation between above-and below-ground growth (Schneider 2022;Wegner 2022). By modifying the soil volume explorable by the rooting system in response to water stress, i.e.…”
Section: Simulating Growth and Function In Variable Environmentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our experimental and modelling results indicate that some of these assumptions need revisiting. We showed that the intensity of water stress, as the result of the growing environment or intra-speci c plant competition, can affect both the maximum rooting depth and the depth at which crops will use water, indicating changes in resource allocation between above-and below-ground growth (Schneider 2022;Wegner 2022). By modifying the soil volume explorable by the rooting system in response to water stress, i.e.…”
Section: Simulating Growth and Function In Variable Environmentsmentioning
confidence: 97%
“…This means that phenotypes that invest resources in deeper roots are likely to pro t from accessing deeper soil water at critical stages around owering and grain lling. We do not know whether the lower yield of hybrid A and B in the higher-yielding environment might be related to the cost of deep roots (Wegner 2022). Root respiration can consume up to 30% of the total plant sugars allocated to the roots (Lambers et al 2003), and faster respiration rates are associated with traits such as high speci c root length, high root nitrogen concentration and ne roots, compared to roots that have high tissue density (Han and Zhu 2021).…”
Section: Phenotypic Plasticity Of Yield and Root Traitsmentioning
confidence: 99%
“…Its source is sugars -a product of photosynthesis occurring in green tissues. In turn, the root system is a "pump" that pumps water and a complex of nutrients from the soil necessary for the development of the above-ground part [1]. If both the "tops" and the "bottoms" work according to the optimal scenario, the agronomist will be satisfied with the crop yields.…”
Section: Introductionmentioning
confidence: 99%
“…This involves intracellular metabolic processes 'consuming' H + (termed 'active buffering'), thus keeping the cytosolic pH in the narrow range slightly above 7 required for cell survival. Apoplastic H + can be mobilized by 'passive' buffering (the extracellular compartment which is in contact with soil solution outsizes the cytosol by several orders of magnitude) and by bicarbonate formation from CO 2 (for details, see Wegner & Shabala, 2020;Wegner et al, 2021;Wegner, 2022). Imposing mild, moderate and severe salinity stress, and using the noninvasive microelectrode ion flux estimation (MIFE) technique, we showed that salinity can induce a steady net H + influx across the root surface, providing first evidence for a key role of the biochemical pH clamp in salt tolerance in maize.…”
Section: Introductionmentioning
confidence: 99%